Obiter (Blackfriars, 1959)
THE ARTS, ARTISTS AND THINKERAS. A S.ymposium edited by John M. CHARLDES DICKENS: THE WORLD OF HIS NOVELSB. By J. Hillis Miller. THE CATHEDRBAL. By Clive Sansom. THE SEVEN HILLS OF THE DOVEB. By Scharmel Iris. HYPHENS. By James Russell Grant. THE GUINNESS BOOK OF POETRY. THE SPIRIT OF THE SPANISH MYSTICSB. By Kathleen Pond.